The Paltera of Miagao, Iloilo social status of women as health providers. - Flores, Eleza F.
With the premise that gender relations shape the role of women health providers in their rspective communities, this study recognizes that the paltera roles of selected women is significant in the villages of Miagao., This traditional birth attendants have persisted as the providers of unique methods in child delivery and more comprehensive and perssonalized support for mothers. In addition, their status indicators (age, length of service, civil status, residency and proficiency) justify their continuity despite the active health care program of the officially-endorsed rural health practitioners (i.e. the midwives).